Investigation of approaches to designing complex database structures in systems of integrated monitoring of environmental, economic, energy and social parameters of the territory - Slipchenko, Volodymyr; Poliahushko, Liubov; Krush, Olha; Rudyk, Volodymyr (Technology audit and production reserves, 2024)
The object of research is the traditional and universal approach of designing the database structure in systems of integrated monitoring of ecological, economic, energy and social parameters of the territory, which include diverse data from various subject areas. In the course of the study, an analysis was performed based on a set of criteria such as scalability, ease of updating data, absence of empty fields, volume of the database, number of tables and fields, ease and speed of execution of requests for a sample set of indicators of the research object. The comparison of these approaches took place on the example of water resources monitoring, since it has several subsystems and a large number of indicators that are used for assessment. It is established that the proposed universal approach to designing complex database structures made it possible to reduce the volume of the database by 2.25 times due to the absence of empty fields. In particular, in the considered example, the filling factor of the database with the traditional approach is 1.75 times less than with the proposed universal approach. It should be noted that the rate of table filling for the traditional design approach can vary depending on the number of indicator values, while the table filling rate for the universal approach is always close to 100 %. Also, the proposed database design approach makes it possible to speed up data loading and processing. For example, with the same volume of significant information, the minimum speed of sampling the characteristics of one research object is 3.87 times greater in a database developed according to the principles of the universal approach than according to the rules of the traditional approach. The proposed structure of the database is successfully used in the system of complex eco-energy-economic monitoring. The developed structure of the database can serve as an effective basis for the formation of an electronic data bank at the level of the enterprise, region and country.